2022
DOI: 10.3390/f13071059
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Temporal Scale Variations in Nighttime Sap Flow Response to Environmental Factors in Ficus concinna over a Subtropical Megacity, Southern China

Abstract: With ongoing climate change and rapid urbanization, the influence of extreme weather conditions on long-term nocturnal sap flow (Qn) dynamics in subtropical urban tree species is poorly understood despite the importance of Qn for the water budgets and development plantation. We continuously measured nighttime sap flow in Ficus concinna over multiple years (2014–2020) in a subtropical megacity, Shenzhen, to explore the environmental controls on Qn and dynamics in plant water consumption at different timescales.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 88 publications
1
4
0
Order By: Relevance
“…The nighttime sap flux has different controlling factors with the daytime sap flux (e.g., Hayat et al, 2021Hayat et al, , 2022Xu & Yu, 2020) (Bo et al, 2017;Zeppel et al, 2004;Zha et al, 2017;Zhang, Xu, et al, 2019). Our results further showed that the hysteresis of ASFD to Rsi is relatively larger than the hysteresis of ASFD to VPD (Figure 11), which is consistent with previous studies under wet soil conditions (e.g., Horna et al, 2011;Phillips et al, 1999).…”
Section: The Relative Importance Of the Environmental Variables On Th...supporting
confidence: 90%
See 3 more Smart Citations
“…The nighttime sap flux has different controlling factors with the daytime sap flux (e.g., Hayat et al, 2021Hayat et al, , 2022Xu & Yu, 2020) (Bo et al, 2017;Zeppel et al, 2004;Zha et al, 2017;Zhang, Xu, et al, 2019). Our results further showed that the hysteresis of ASFD to Rsi is relatively larger than the hysteresis of ASFD to VPD (Figure 11), which is consistent with previous studies under wet soil conditions (e.g., Horna et al, 2011;Phillips et al, 1999).…”
Section: The Relative Importance Of the Environmental Variables On Th...supporting
confidence: 90%
“…The nighttime sap flux has different controlling factors with the daytime sap flux (e.g., Hayat et al, 2021, 2022; Xu & Yu, 2020), thus, the modelling effort in our work by separately calculating daytime and nighttime sap flux shows potential to improve the overall sap flux modelling. Our measurements showed that total nighttime sap flux correlates positively with total daytime sap flux, confirming our previous hypothesis for the model development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The physiological structure of plants (such as leaf area index, sapwood, crown width, and phenology) determines their potential for transpiration [15][16][17][18]. Environmental factors that impact V include meteorological factors, such as temperature (Ta), total solar irradiance (TSI), relative humidity (RH), vapour pressure deficit (VPD), wind speed (WS), and precipitation (P), which determine the instantaneous changes in transpiration and are the main driving force of canopy transpiration [19][20][21][22][23][24], and soil factors, such as soil moisture content and soil temperature, which determine the peak and total transpiration of plants [25][26][27]. In particular, when soil moisture is limited, the hydraulic resistance of the soil and roots increases, leading to delayed water transport and stomatal closure [28,29].…”
Section: Introductionmentioning
confidence: 99%